2007
DOI: 10.1097/01.mpg.0000239737.64240.72
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Video Capsule in Pediatric Patients With Functional Abdominal Pain

Abstract: The results of this small cohort suggest that in children with FAP, VCE is more sensitive than EGD for detection of macroscopic gastric and small bowel pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 32 publications
(49 reference statements)
2
31
0
1
Order By: Relevance
“…Findings from traditional radiological and endoscopic examinations were normal, which led us to performed CE when she was 10 years of age. Among the five patients with suspected CD, one ( 3) had prolonged fever with multiple aphthous ulcers in the colon that were identified by colonoscopy, one ( [9][10][11][12] with RAP, the laboratory examinations were normal, and there were no parasites or pathogenic bacteria. In addition, traditional radiological and endoscopic findings were normal or insufficient to detect small intestinal lesions; consequently, we performed CE to screen for small intestinal lesions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings from traditional radiological and endoscopic examinations were normal, which led us to performed CE when she was 10 years of age. Among the five patients with suspected CD, one ( 3) had prolonged fever with multiple aphthous ulcers in the colon that were identified by colonoscopy, one ( [9][10][11][12] with RAP, the laboratory examinations were normal, and there were no parasites or pathogenic bacteria. In addition, traditional radiological and endoscopic findings were normal or insufficient to detect small intestinal lesions; consequently, we performed CE to screen for small intestinal lesions.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of adult patients have revealed that CE is superior to the small bowel series for evaluating the small intestine [1][2][3]. A number of recent studies on pediatric patients have demonstrated that CE is also a useful in children with abdominal complaints, although the application of CE in this patient population has received relatively less attention compared to the adult patient population [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The indications for CE in both children and adults include obscure gastrointestinal bleeding (OGIB), Crohn's disease (CD), and lymphangiectasia; in adults, suspected tumors of the small bowel also suggest the need for CE [9,[12][13][14].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on previous studies in adult population, CE doesn't provide diagnostic value against www.intechopen.com abdominal pain itself, and strict patient selection on the basis of additional symptoms of signs is the key to increasing the field to capsule endoscopy in patients with chronic abdominal pain. In regard to children, a previous study reported that CE detected small bowel involvement in 1/10 patients with functional abdominal pain and most of patients don't have the related organic etiology (Shamir, 2007). Another pediatric study described that 6/12 patients with abdominal pain had abnormal findings in which 3 with small bowel CD, 2 lymph nodular hyperplasia, and 1 blue rubber bleb syndrome, however it is undescribed whether those patients had additional symptoms or signs (Fritscher-Ravens, 2009).…”
Section: Abdominal Painmentioning
confidence: 99%
“…Often, we are able to select those patients who will readily swallow the capsule (using candies of increasing sizes) and train some who were afraid to swallow big candies [26] . When the patient can not swallow the capsule due to any reason (including swallowing disorders, dysphagia, gastroparesis) the capsule can be safely introduced to the duodenum using various techniques and a standard endoscope (Figure 1) [20,27] .…”
Section: Advantages and Limitationsmentioning
confidence: 99%